FRI0119 Improvement in some, but not all, surrogate measures of cardiovascular disease following intensive treatment of early rheumatoid arthritis. (23rd January 2014) - Bissell, L.-A.; Mackie, S.L.; Kozera, L.; Nam, J.; Burska, A.; Hensor, E.M.; Keen, H.; Villeneuve, E.; Donica, H.; Conaghan, P.; Andrews, J.; Emery, P.; et al.
Abstract : Background: Patients with rheumatoid arthritis (RA) have an elevated risk of cardiovascular disease (CVD), predominantly ischaemic heart disease (IHD). Systemic inflammation is thought to be a key contributor to this risk and it is hoped early therapeutic suppression of inflammation will reduce cardiovascular (CV) events in the long term. Insulin resistance, associated with metabolic syndrome, N-terminal pro-brain natriuretic peptide (NT-proBNP) and atherogenic lipid profiles have been proposed as potential surrogate measures of atherosclerosis in RA. Each has been shown to correlate with systemic inflammation, but their utility in RA above measurement of the acute phase response remains unknown. Objectives: To determine whether suppression of inflammation in early RA influences surrogate measures of atherosclerosis, including the homeostasis model assessment of insulin resistance (HOMA-IR), NT-proBNP and dyslipidaemia. Methods: CRP, fasting glucose and lipids, and in a sub-group, NT-proBNP and fasting insulin, were measured at baseline and week 26 in DMARD naïve RA patients, with 3-12 months symptoms, recruited into the Infliximab as Induction therapy for Early rheumatoid Arthritis (IDEA) multicentre double-blind randomised controlled trial. Patients met the 1987 ACR criteria. Treatment was randomised to IFX +MTX or MTX with 250mg IV methylprednisolone as induction therapy. 120mg IM methylprednisolone was given if DAS>2.4 at 3 time points within the first 26 weeks. HOMA-IR was calculated at each time point. Descriptive statistics, Wilcoxon and paired t-test, and Spearman's correlation were performed. Results: Data from 112 patients (69% female, mean age 53 years, 55% RF and 70% anti-CCP positive) were analysed. At baseline, 9% were on a statin and 14% an anti-hypertensive agent. 4 patients had known IHD and were excluded from the subsequent analysis. The median (range) CRP was 13mg/l (0-30) with CRP normal (<5.0mg/l) in 33%. Baseline CRP negatively correlated with HDL (rho -2.78, p=0.024) and total cholesterol (TC) (rho -2.33, p=0.026). 15%, 30%, 39%, and 25% had at risk levels for HDL, LDL, TC and triglyceride (TG), respectively 1 . In the subgroup of 79 patients with data on NT-proBNP and fasting insulin, 17% and 38% of patients had raised levels of NT-proBNP and HOMA-IR, respectively. Comparing week 26 to baseline, there was a significant fall in CRP (p<0.001; normal levels in 64%) and HOMA-IR (p=0.008; abnormal in 19%), but not NT-proBNP (p=0.132; elevated in 17%). With respect to the dyslipidaemia, HDL and TC rose (p<0.001 and p<0.001 respectively), but there was no significant change in LDL or TG. 5%, 46%, 61%, and 20% had at risk levels for HDL, LDL, TC and TG, respectively. Conclusions: In this study, suppression of inflammation was associated with improvement in insulin resistance and increased HDL, but no significant change in NT-proBNP, TG or LDL following 26 weeks intensive RA treatment. Further analyses of biomarkers at week 78 and drug specific effects are underway. Long term follow up is being performed to determine if those patients with persistently abnormal CV biomarkers develop subclinical or overt CVD in the future despite intensive early treatment for RA. References: JAMA. 2001;285(19):2486-97 Disclosure of Interest: L.-A. Bissell: None Declared, S. Mackie: None Declared, L. Kozera: None Declared, J. Nam: None Declared, A. Burska: None Declared, E. Hensor: None Declared, H. Keen: None Declared, E. Villeneuve: None Declared, H. Donica: None Declared, P. Conaghan: None Declared, J. Andrews: None Declared, P. Emery: None Declared, A. Morgan Grant/Research support from: Supported in part by a research grant from Investigator-Initiated Studies Program of Merck Sharp & Dohme Limited. The opinions expressed in this paper are those of the authors and do not necessarily represent those of Merck Sharp & Dohme Limited